The Film-Forming Characterization and Structural Analysis of Pectin from Sunflower Heads. (10th February 2021) - Peng, Xiaoxia; Yang, Guang; Yue, Qi; Ren, Xiaomeng; Zhou, Yifa; Zhang, Mengshan
Abstract : A natural low-methoxyl pectin (termed AHP, DM = 25.9 % ) was extracted from dried heads of sunflower and showed better film-forming performance blended with hydroxypropyl methylcellulose (HPMC). The solutions and films of different HPMC/AHP blends were characterized by viscosity, transparency, mechanical properties, loss on drying, water drop penetration time (WDPT), disintegration and SEM. In order to analyze the structure-property relationship of film forming, AHP was separated by ion-exchange chromatography and characterized. The results showed that the blends were immiscible, but the formation of AHP gel would give the blended film better mechanical properties. AHP was fractionated into one neutral fraction and two acidic fractions (AHPA-1 and AHPA-2). The analytical results showed that AHPA-1 and AHPA-2 were identified to be homogalacturonan- (HG-) rich pectins with low DM, and the molecular weights of them were estimated to be 106 kDa and 226 kDa, respectively. Due to the high content of the HG domain, low DM and high molecular weights, AHP had excellent gelling properties induced by Ca 2+ and was added to improve the film-forming properties of HPMC and to develop plant hollow capsules.